Ab initio calculations of the phase behavior and subsequent magnetostriction of Fe1−xGax within the disordered local moment picture - Marchant, GA; Woodgate, CD; Patrick, CE; Staunton, JB (American Physical Society, 2021)
A holistic approach for studying both the nature of atomic order and finite-temperature magnetostrictive behavior in the binary alloy Galfenol (Fe1−xGax, 0≤x≤0.25) is presented. The phase behavior is studied via atomistic modeling with inputs from ab initio calculations, and the ordered phases of interest at nonstoichiometric concentrations are verified to exhibit B2- and D03-like order. The finite-temperature magnetoelasticity of these phases, in particular the magnetoelastic constant B1, is obtained within the same ab initio framework using disordered local moment theory. Our results provide an explanation for the origin of the experimentally observed peak and subsequent fall in the material's magnetostriction at x∼0.19, which has been disputed. In addition, we show that it is possible to enhance the magnetostriction of D03−Fe3Ga by removing a small fraction of electrons from the system, suggesting that a Fe-Ga-Cu or Fe-Ga-Zn alloy could exhibit greater magnetostrictive properties than Galfenol.